2015
DOI: 10.1089/omi.2015.0009
|View full text |Cite
|
Sign up to set email alerts
|

Blood Metabolome Changes Before and After Bariatric Surgery: A1H NMR-Based Clinical Investigation

Abstract: Excessive body fat and obesity have adverse health effects and result in significant morbidity such as type 2 diabetes mellitus. The health burden of obesity can be reduced with the Roux-en-Y gastric bypass (RYGB) weight-loss bariatric surgery. Little is known on the molecular changes that occur at the metabolome level before and after bariatric surgery, with a view to clinical biomarker development. Hence, we employed a metabolomics approach in 10 obese diabetic patients who underwent bariatric surgery. Metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 48 publications
(48 reference statements)
7
51
0
Order By: Relevance
“…Serum C15:0 FA increased significantly at 6 months post‐RYGB compared with pre‐surgery values. A similar increase of serum C15:0 at 1 year post‐RYGB has been previously reported . Plasma odd chain saturated FA (such as C15:0 and C17:0) have a positive association with dairy fat intake while an inverse association exists with development of cardiovascular disease and type 2 diabetes .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Serum C15:0 FA increased significantly at 6 months post‐RYGB compared with pre‐surgery values. A similar increase of serum C15:0 at 1 year post‐RYGB has been previously reported . Plasma odd chain saturated FA (such as C15:0 and C17:0) have a positive association with dairy fat intake while an inverse association exists with development of cardiovascular disease and type 2 diabetes .…”
Section: Discussionsupporting
confidence: 83%
“…A significant increase in C14:0 and C18:0 FA at 6 months post‐RYGB was also observed in the present study. Similarly, Lopes et al reported significant increase of C14, C18 at 1 year post‐RYGB . Significant changes in essential FA or omega 3 FA were not observed following RYGB, even though those are known to be reduced after bariatric surgery .…”
Section: Discussionmentioning
confidence: 90%
“…Others clinical information about the subjects and metabolic alterations associated with the basal metabolism can be found in Lopes et al (2015). In this study, the timeresolved 1 H NMR-based metabolomic approach was used to expand the ''static'' information normally provided by metabolomic studies.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a hydrogen nuclear magnetic resonance ( 1 H NMR) metabolomic profiling study showed alterations of basal metabolism among overweight diabetic subjects after RYGB, and these alterations were associated with energy homeostasis (decreased glucose and increased lactate and acetate levels), 1 decreased branched-chain amino acids (BCAA), and changes in lipid metabolism (Lopes et al, 2015). Similarly, mass spectrometry-based metabolomics applied to patients with RYGB (Laferrère et al, 2011;Lindqvist et al, 2013;Mutch et al, 2009) revealed that oral versus gastric mixed-meal tolerance test (MMTT) showed higher incretin and insulin responses after oral MMTT (Lindqvist et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has found recent broad applications in both preclinical and clinical research (Embade et al, 2016;Kim et al, 2011;Lindeque et al, 2015;Lopes et al, 2015). The metabolome, one of the end products of gene-environment interactions immediately upstream to their phenotypic impacts, can help characterize and discriminate pathophysiological signatures of AD (Sapkota et al, 2015), PD (Hatano et al, 2016), and ALS (Blasco et al, 2016).…”
Section: Introductionmentioning
confidence: 99%